Makna Self-Healing pada Yayasan Rangkoel Care Indonesia - Bella Maulina; Atie Rachmiatie (UNISBA Press, 2023)
Abstract. This research was conducted based on the existence of a phenomenon regarding the existence of misinterpretation among the people, especially Generation Z regarding the meaning of